Sistem Informasi Pendataan Engine Alat Berat Komatsu Berbasis Web - William Julio Ch Kutani; Widia Puspita (Publikasi Indonesia, 2023)
PT United Tractors Tbk is the largest and leading heavy equipment distributor company in Indonesia which holds well-known product brands such as Komatsu, UD Trucks, Scania, BOMAG and Tadano. Currently the PT United Tractors Makassar branch workshop still uses the manual method for data collection of heavy equipment engine books, this is felt to be less effective and efficient because the mechanics are impractical in utilizing existing technology and the processing time and engine analysis will definitely take more time long. This study aims to make it easier for mechanics to work on heavy equipment engines without having to carry hardcopies of money needed in the field because mechanics only need to open a PDF file in the program. The final result of this research is to create a web-based application program system that is used as a data collection process for heavy equipment engine books.